3-Dimensional finite element modelling of asphalt mixtures for thermal conductivity determination. Issue 6 (12th May 2022) - Chu, Longjia; He, Lei; Fwa, Tien Fang
ABSTRACT: Laboratory determination of the thermal conductivity k of asphalt materials is time consuming. Numerical determination of k is more viable practically for the purpose of mix design and paving temperature control. Researchers have applied microstructure finite element models for k determination. The method requires modelling skills and is computational resources demanding. This study shows that a simple row-column finite-element model of cubical cells can be employed to predict k with the same level of accuracy as microstructure models. Based on theoretical considerations of heat conduction mechanism and the construction and paving process of asphalt mixtures, this study reveals that exact mixture microstructure representation is unnecessary and impractical for the k determination problem. The simple proposed model, having straight-forward finite-element mesh representation and high computational efficiency, offers a practical tool for k determination to enable timely thermal evaluation of mix design, temperature analysis for paving control, and structural behaviour study under thermal loading.